2021
DOI: 10.1002/hbm.25366
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal dynamic functional connectivity is linked to recovery after acute ischemic stroke

Abstract: The aim of the current study was to explore the whole‐brain dynamic functional connectivity patterns in acute ischemic stroke (AIS) patients and their relation to short and long‐term stroke severity. We investigated resting‐state functional MRI‐based dynamic functional connectivity of 41 AIS patients two to five days after symptom onset. Re‐occurring dynamic connectivity configurations were obtained using a sliding window approach and k‐means clustering. We evaluated differences in dynamic patterns between thr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 71 publications
4
35
0
Order By: Relevance
“…The BOLD time series that were extracted from 86 regions of FreeSurfer atlas (same atlas used for static FC and SC analysis) were used as an input to the GIFT toolbox. As suggested by Allen et al (2014) and previous studies (Bonkhoff et al, 2020(Bonkhoff et al, , 2021, dFC between two regional time courses was computed using a sliding window approach with a window size of 22 TR (50.6 s) in steps of 1 TR (2.3 s). A rectangular window of 22 time points convolved with a Gaussian of 3 TR (6.9 s) was used for tapering along the edges, resulting in 153 tapered time windows per subject.…”
Section: Dynamic Fc Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The BOLD time series that were extracted from 86 regions of FreeSurfer atlas (same atlas used for static FC and SC analysis) were used as an input to the GIFT toolbox. As suggested by Allen et al (2014) and previous studies (Bonkhoff et al, 2020(Bonkhoff et al, , 2021, dFC between two regional time courses was computed using a sliding window approach with a window size of 22 TR (50.6 s) in steps of 1 TR (2.3 s). A rectangular window of 22 time points convolved with a Gaussian of 3 TR (6.9 s) was used for tapering along the edges, resulting in 153 tapered time windows per subject.…”
Section: Dynamic Fc Analysismentioning
confidence: 99%
“…Dynamic FC (dFC) approaches allow assessment of the varying topology of FC over time by using sliding windows to assess dynamic FCs (Allen et al, 2014 ). There is increased interest in using dFC to investigate pathological mechanisms in psychiatric disorders, and stroke (Damaraju et al, 2014 ; Rashid et al, 2016 ; Sambataro et al, 2017 ; Mennigen et al, 2018 ; Bonkhoff et al, 2020 , 2021 ). In MS, recent studies have used dFC to (1) compare clinically isolated syndrome (CIS) patients to HC (Rocca et al, 2019 ), (2) analyze relationships with information processing speed in relapsing-remitting (RR) pwMS (van Geest et al, 2018 ), and (3) classify cognitively impaired vs. preserved pwMS (d'Ambrosio et al, 2019 ; Eijlers et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…As dFC analysis can extract more time-varying characteristics of information exchange between brain regions on a time scale and because these characteristics are significantly related to many physiological parameters ( 12 ), pathological features ( 13 ), and even intervention effects ( 14 ), dFC analysis seems to be particularly suitable for evaluating the complex and changeable characteristics of brain networks after stroke and exploring the neural mechanism of functional rehabilitation. Previous studies have shown that the proportion between integrated and segregated states was not balanced in patients who suffered from strokes ( 4 ) and that the temporal dynamics of FC were closely related to clinical severity ( 15 , 16 ). However, these studies focus mainly on patients with acute or chronic stroke; there are few reports on the dynamic relationship between brain networks in patients with a convalescence period of 1–3 months after stroke.…”
Section: Introductionmentioning
confidence: 99%
“…All analyses were adjusted for variation that could be explained by age, age 2 , sex, education in years, pre-morbid cognitive performance, and total lesion volume. We also included sex as a covariate in the model to explicitly account for a-priori differences between female and male stroke outcomes (Bonkhoff, Schirmer, Bretzner, Hong, et al, 2021). For example, worse language outcomes in females could be linked to an underlying cause independent of the lesion distribution, such as a decreased likelihood of receiving acute interventions.…”
Section: Resultsmentioning
confidence: 99%